The Influence of Service Quality and School Facilities on Teacher Performance in Public Elementary Schools in Huta Raja Tinggi Subdistrict, Padang Lawas Regency - Fitriani; Ali Mukti Tanjung; M. Ali Musri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The aim of this research is to determine the extent of the influence of service quality and school facilities on teacher performance in elementary schools in the Huta Raja Tinggi Subdistrict, Padang Lawas Regency. The research uses a quantitative approach. The population consists of 317 individuals, with a sample size of 63 teachers. The analysis method used is quantitative analysis with the SPSS 25 application. The research findings show that the influence of service quality on teacher performance is significantly 65.3%. This indicates that the better the service quality, the higher the teacher performance. Meanwhile, the influence of school facilities on teacher performance is significantly 31.8%. The research findings imply that the better the school facilities, reflected in work tools, work equipment, and social facilities, the better the teacher performance. Additionally, the combined influence of service quality and school facilities on teacher performance is 89.8%, while the remaining 10.2% is influenced by other variables not tested in this study.